Editing of the mitochondrial small subunit rRNA in Physarum polycephalum. - Mahendran, R (1994)
Post-transcriptional insertion, substitution or deletion of nucleotides in RNA (RNA editing) has been observed in RNAs from a number of organisms but always in messenger RNA or transfer RNA. We report here that the 17S rRNA of the mitochondrial ribosome of Physarum polycephalum is edited at 40 sites with single cytidine insertions. The locations of the editing sites are fairly evenly distributed throughout the RNA and do not correspond to any obvious feature of the primary sequence or secondary structure. In addition to these cytidine editing sites are editing sites in which a nucleotide other than cytidine is inserted. At two sites a uridine is inserted and at two sites adenosine residues are inserted. This is the first report of mixed nucleotide insertional editing. These results imply that the editing mechanism in Physarum may be different from those proposed for the kinetoplastid protozoa.